2022
DOI: 10.1177/1934578x221099970
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanin Extraction Method and Sample Preparation Affect Anthocyanin Yield of Strawberries

Abstract: Anthocyanins are a group of pigments with antioxidant activities that are present naturally in plants. The role of the pigment in human health and its quantitative analysis has attracted a lot of attention globally. A well-known and accurate method of anthocyanin quantification is based on spectrophotometric methods. However, these methods are subject to interference from impurities and need to be optimized for different plant matrixes and extraction conditions. Two experiments were designed to study (1) the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
(79 reference statements)
0
6
0
Order By: Relevance
“…It was reported elsewhere that anthocyanins are highly soluble in water. Their polyphenolic compounds increase the hydrophobic characteristic, which makes them soluble in organic solvents (38). Furthermore, compared to recently reported natural sensitizers using similar samples and solvents, our power conversion efficiencies of the produced devices are slightly inferior (1,28).…”
Section: Dssc Performancementioning
confidence: 70%
“…It was reported elsewhere that anthocyanins are highly soluble in water. Their polyphenolic compounds increase the hydrophobic characteristic, which makes them soluble in organic solvents (38). Furthermore, compared to recently reported natural sensitizers using similar samples and solvents, our power conversion efficiencies of the produced devices are slightly inferior (1,28).…”
Section: Dssc Performancementioning
confidence: 70%
“…According to annotations, 69% of PsbHLHs were participating in the regulation of biological processes. Anthocyanins are naturally occurring plant pigments with antioxidant properties ( Taghavi et al., 2022 ). Previous research has demonstrated that TT8 regulates anthocyanin biosynthesis ( Ahn et al., 2022 ), and it has been speculated that the homologous gene PsbHLH103 participates in anthocyanin synthesis in P. sibirica .…”
Section: Discussionmentioning
confidence: 99%
“…The anthocyanins have several different structures owing to their reversible transformation with the change in pH of the buffer solution, while the other interferers have no such change. The anthocyanins were present in the form of red closing cations at pH 1.0, while they were colorless semi-acetals or colorless chalcones at pH 4.5 in the buffer solution [ 20 ]. Cypermethrin-3-glucoside was usually used as the reference to quantify the anthocyanins, while most of the anthocyanins in the tested PSPs were highly glycosylated and acylated paeoniflorin anthocyanins, which played an important role in the stability of these phenolics.…”
Section: Methodsmentioning
confidence: 99%